Analysis of the Impact Education to Interest and Effected to Entrepreneur Success for Students - Faisal, Rahman; Anthoni, Lukman (AGUSPATI Research Institute, 2021)
The aims in this research to determine the learning effect of entrepreneurship education has impact to entrepreneurial interest and Effected to entrepreneur success for studnent. This research uses descriptive quantitative method. Data obtained from the results of questionnaires that have been filled in by respondents who are students at universities or colleges as the research samples. The population used in this study was determined to be students and female students who have received entrepreneurship courses. The use of samples in this research is using the Slovin method. The sample used in this study who are currently taking higher and moderate education or who have received entrepreneurship-learning material. Meanwhile, data analysis it was performed using descriptive statistics and PLS-Structural Equation Modeling (PLS-SEM) using SmartPLS software. The results have showed that entrepreneurship education (X) had significant effect to Y (Interest) of 0.513 and Y (Interest) has impact to (Z) Entrepreneur Success is 0.597. So it can be concluded that in this research it was found that entrepreneurship education has significance for entrepreneur interest and entrepreneur interest has has significance for entrepreneur success for students.